Investigating the Influence of Information Overload on Millennial Purchase Intent in the Java Online Market - Dwi Anna Kristanti; Novelia Asita Mranani (Master of Management, School of Business and Management, Petra Christian University, 2025)
This study aims to examine the impact of information overload on the purchase behavior of millennials residing in Java. This study investigates the potential factors contributing to information overload with a focus on online reviews and website layouts. This study aims to examine the relationships between online reviews, website design, and information overload, utilizing a theoretical framework grounded in information foraging theory and information processing theory. Employing partial least squares analysis, the primary objective is to examine the effects of Internet reviews and website designs on information overload and its subsequent influence on millennials' purchasing intentions. The study's findings reveal that internet reviews cause information overload, demonstrating an inverse relationship. Website design plays a crucial role in generating and strongly influencing information overload. This excess information has a significant impact on millennials’ purchasing decisions. The results elucidate the complex interrelationship between online reviews, website layouts, information saturation, and consumer behavior, thereby providing valuable insights into consumer behavior in the digital marketplace.